SCN1A-Related Epilepsy: Novel Mutations and Rare Phenotypes - Ma, Rui; Duan, Yiran; Zhang, Liping; Qi, Xiaohong; Zhang, Lu; Pan, Sipei; Gao, Lehong; Wang, Chaodong; Wang, Yuping (Frontiers in Molecular Neuroscience, 2022)
Objectives: To expand the genotypes and phenotypes of sodium voltage-gated channel alpha subunit 1 (SCN1A)-related epilepsy. Methods: We retrospectively collected the clinical and genetic information of 22 epilepsy patients (10 males, 12 females; mean: 9.2 ± 3.9 years; 3.9-20.3 years) carrying 22 variants of SCN1A. SCN1A mutations were identified by next-generation sequencing. Results: Twenty-two variants were identified, among which 12 have not yet been reported. The median age at seizure onset was 6 months. Sixteen patients were diagnosed with Dravet syndrome, two with genetic epilepsy with febrile seizures plus (one evolved into benign epilepsy with centrotemporal spikes (BECTS)), one with focal epilepsy, one with atypical childhood epilepsy with centrotemporal spikes (ABECTS) and two with unclassified epilepsy. Fourteen patients showed a global developmental delay/intellectual disability (GDD/ID). Slow background activities were observed in one patient and epileptiform discharges were observed in 11 patients during the interictal phase. Significance: This study enriches the genotypes and phenotypes of SCN1A-related epilepsy. The clinical characteristics of patients with 12 previously unreported variants were described.